Bio-hydrogen production from steam reforming of liquid biomass wastes and biomass-derived oxygenates: A review - Chong, C.C. (Elsevier Ltd, 2022)
Alternative energy sources have been the main interest since past decades due to inclining energy demand and growing environmental consciousness. Hydrogen (H2) which is known as a clean fuel and most viable energy carrier for the future, is highly potential due to its high mass-based energy density. Among the diverse thermochemical techniques introduced to generate H2 in an economical way, steam reforming (SR) emerged as a promising option due to high H2 production ability and economical profit. Presently, the feedstocks for mature SR technology are mostly non-renewable resources such as fossil fuel (coal, diesel, gasoline, and natural gas). H2 can also be produced from SR from alternative feedstocks such as liquid biomass waste and biomass derived oxygenates. This approach will not only solve disposal problem, but also open new breakthrough for renewable resources utilization. In this review, the concept, advantages, prospects and challenges of bio-H2 production via SR process over industrial effluents, solvents, biomass-derived solvents, and lipids are reviewed. These organic-rich feedstocks are mostly waste that caused pollution issues or produced in glut, thus proper utilization of these materials is an urgent need. SR of these alternative feedstocks are viable due to the high H2 yields obtained upon the transformation of their high-water volume content. Â© 2021